Characterization of a caveolin‐1 mutation associated with both pulmonary arterial hypertension and congenital generalized lipodystrophy. (2nd November 2016) - Han, Bing; Copeland, Courtney A.; Kawano, Yumeko; Rosenzweig, Erika Berman; Austin, Eric D.; Shahmirzadi, Layla; Tang, Sha; Raghunathan, Krishnan; Chung, Wendy K.; Kenworthy, Anne K.
Abstract : Congenital generalized lipodystrophy (CGL) and pulmonary arterial hypertension (PAH) have recently been associated with mutations in the caveolin‐1 ( CAV1 ) gene, which encodes the primary structural protein of caveolae. However, little is currently known about how these CAV1 mutations impact caveolae formation or contribute to the development of disease. Here, we identify a heterozygous F160X CAV1 mutation predicted to generate a C‐terminally truncated mutant protein in a patient with both PAH and CGL using whole exome sequencing, and characterize the properties of CAV1, caveolae‐associated proteins and caveolae in skin fibroblasts isolated from the patient. We show that morphologically defined caveolae are present in patient fibroblasts and that they function in mechanoprotection. However, they exhibited several notable defects, including enhanced accessibility of the C‐terminus of wild‐type CAV1 in caveolae, reduced colocalization of cavin‐1 with CAV1 and decreased stability of both 8S and 70S oligomeric CAV1 complexes that are necessary for caveolae formation. These results were verified independently in reconstituted CAV1 −/− mouse embryonic fibroblasts. These findings identify defects in caveolae that may serve as contributing factors to the development of PAH and CGL and broaden our knowledge of CAV1 mutations associated with human disease. Abstract : We identify a heterozygous F160X mutation in the caveolin‐1 ( CAV1 ) gene in a patient with both pulmonary arterial hypertension (PAH) and congenital generalized lipodystrophy (CGL) and examine its effect on caveolae assembly. We find that the mutant protein forms hybrid caveolae together with wild‐type CAV1 in patient skin fibroblasts and reconstituted CAV1 −/− murine embryonic fibroblasts but that these caveolae are abnormal in several respects. These caveolaer defects may serve as contributing factors to the development of PAH and CGL.